PENEGAKAN HUKUM TINDAK PIDANA NARKOTIKA OLEH KEPOLISIAN DAERAH LAMPUNG: ANALISIS HAMBATAN DAN STRATEGI PENGUATAN PENYIDIKAN - Berthiana Berthiana; Januri Januri; Rika Santina (Universitas Labuhanbatu, 2026)
The increasing prevalence of narcotics abuse and illicit trafficking in Lampung Province poses a serious threat to public security, social order, and the effectiveness of Indonesia's criminal justice system. This condition requires strengthening law enforcement efforts that extend beyond punitive measures to address the various challenges encountered during criminal investigations. This study aims to analyze the enforcement of narcotics laws by the Lampung Regional Police (Polda Lampung), identify the factors hindering the effectiveness of criminal investigations, and formulate strategies to strengthen investigative processes. The research employs a normative-empirical (socio-legal) approach using statutory and case approaches, supported by library research, document analysis, and interviews with investigators at the Lampung Regional Police. The findings reveal that narcotics law enforcement has been implemented through both preventive and repressive measures. However, the effectiveness of investigations remains constrained by limited human resources, inadequate investigative facilities and technology, the complexity of organized narcotics trafficking networks, and insufficient inter-agency coordination. This study argues that strengthening investigators' professional capacity, modernizing investigative technologies, enhancing inter-agency collaboration, and optimizing community-based prevention programs constitute key strategies for improving the effectiveness of narcotics law enforcement in Lampung Province. Keywords: law enforcement; narcotics crime; Lampung Regional Police; criminal investigation; investigation strengthening strategy